Understanding the role of cognitive constructs employed in reading in global math and science achievement - Arastaman, Gökhan; Bulus, Metin; Kontaş, Hakkı; Özcan, Bahadır (Frontiers in Psychology, 2024)
We utilized PISA-2018 data from 71 countries to investigate the relationship between cognitive constructs employed in reading literacy (locating information, understanding, evaluating and reflecting, single and multiple thinking) and, math and science achievement. We found that locating information, understanding, evaluating and reflecting, single and multiple thinking collectively accounted for 56% of the variance in math and 63% in science achievement, even after adjusting for gender, socioeconomic status, and country fixed effects. This means majority of cultural differences in math and science achievement (resulting from different education systems) can be explained by cognitive constructs employed in reading. We also noted that, at the country level, components of cognitive constructs demonstrated an interesting reconciliatory pattern. Countries with lower scores in "locating information" subscale tended to score higher in "understanding" and "evaluation and reflection" subscales. Similarly, countries scoring higher in "understanding" subscale were associated with lower scores in "evaluation and reflection" subscale. These findings are particularly significant for STEM interventions aiming to enhance math and science achievement, as they indicate that a substantial portion of the variance in these achievements can be explained by locating information, understanding, evaluating and reflecting, single and multiple thinking employed in reading. Therefore, schools should consider modifying their curriculum to integrate cognitive constructs employed in reading more into math and science education.